Anxiety Level of DKI Jakarta Women’s Rugby Athletes Towards the National Sports Week 2024 - Putrianingsih, Shalza; Wiradihardja, Sudradjat; Widyaningsih, Heni (Sports Medicine Curiosity Journal, 2023)
To achieve maximum performance, an athlete requires preparation such as physical, technical, tactical and mental. One of the mental aspects of sports psychology is anxiety. Anxiety is a mental symptom that is identical to negative feelings which are characterized by feelings of worry, tension, and unease when facing a situation, causing a decrease in concentration and self-confidence. This study aims to determine the anxiety level of DKI Jakarta female rugby athletes before the match. This research is a quantitative descriptive research using a percentage formula. Data collection used a questionnaire with research instruments using the Sport Competition Anxiety Test (SCAT). The population in this study were all female rugby athletes from DKI Jakarta, totaling 15 athletes who were designated as the research sample. The research results showed that the anxiety level of DKI Jakarta female rugby athletes before the match was 27% (4) athletes who had low anxiety levels, 60% (9) athletes had moderate anxiety levels, and 13% (2) athletes had high anxiety levels. From the data results, it can be explained that the anxiety level of DKI Jakarta female rugby athletes before the match is in the medium category.